Main reasons that influence students to migrate from their first major to the Major of Modern Languages, at the Foreign Language Department, at the University of El Salvador, in the period of 2008 – 2013 - Andaluz Recinos, Víctor Manuel; Salinas Centeno, Alexander Ernesto; Velásquez Díaz, Lessyrinereira; Salazar Murcia, Pedro Antonio; Nicolas Ayala Edgar (San Salvador, El Salvador : Universidad de El Salvador, 2014)
Nowadays, thousands and thousands of High School graduates are willing to continue their higher education at the University. However, the University of El Salvador remains the only public University in the country. Consequently, it does not have enough capacity to host all of students assessed due to the fact that the capacity it has is approximately the fifty percent of all the population can be accepted. The University of El Salvador, by far, hosts the largest population of students in the country. As a consequence, some Schools and Departments are directly affected by students´ population growth. As a consequence, the Foreign Language Department is one of the most affected Departments at the University due to it has the largest academic unit at the School of Sciences and Humanities compared to other Schools and Departments. For the researchers then, to identify the reasons that motivated students to migrate from their first major choice when entering the University to the Major of Modern Languages is crucial because through this issue, the administrators of the Foreign Language Department can take needed preventions by looking for the most suitable solutions for all those involved students in this process. At the same time, specific internal policies are established as well as the best processes on how and where students must start the process of major changes by talking into consideration the legal requirements that the University demands. Therefore, for many accepted students, to keep on their first major choice represents a spot for another student to enter to the only public University of El Salvador by maximizing resources for all those who want a higher education.
Anexos.
Bibliografía : hojas 60-61
Keywords: Inglés -- Enseñanza; Cambios de carrera